313 No more frozen section for preoperative diagnoses of atypical endometrial hyperplasia. (13th November 2020) - Almeida, J; Ruiz-esquide, M; Luco, M; Grez, I; Miranda, V; Orlandini, E
Abstract : Introduction: The association between atypical endometrial hyperplasia(AH) and cancer is well established. The objective of this study was to evaluate the frequency of endometrial cancer and the accuracy of frozen section (FS) among patients with preoperative diagnosis of AH. Methods: A retrospective review of patients with preoperative diagnosis of atypical endometrial hyperplasia, treated with hysterectomy was performed at Hospital Clinico Pontificia Universidad Catolica de Chile, between 03/2011 and 03/2020. The frequency of cancer and accuracy of FS was calculated. Results: 88 patients with preoperative diagnosis of atypical endometrial hyperplasia were treated with hysterectomy in our center on the mentioned dates. Final pathological examination revealed endometrial cancer in 12/88 women (13, 6%), and only 3 had high risk characteristics (G2-G3, > 50% myometrial invasion) Frozen section analysis was performed in 75/88 patients (87, 5%), which included all patients who had a final diagnosis of cancer. FS analysis identified 6/12 patients (50%) with endometrial cancer, none of them changed surgical plan. The sensitivity and specificity of FS analysis was 50% (95% CI 21, 09–78, 91%) and 100% (95% CI 95, 26–100%) respectively. The positive and negative predictive value for FS analysis was 100% and 92, 68% (95% CI 87, 8–95, 7%) respectively. Conclusion: In our center a low proportion of patients had concomitant cancer at time of hysterectomy. We recommend not performing FS since it increases operative time, costs and did not change the surgical plan in any of the patients with preoperative diagnosis of atypical hyperplasia.